Transpiling Quantum Assembly Language Circuits to a Qudit Form - Denis A. Drozhzhin; Anastasiia S. Nikolaeva; Evgeniy O. Kiktenko; Aleksey K. Fedorov (Entropy, 2024)
In this paper, we introduce the workflow for converting qubit circuits represented by Open Quantum Assembly format (OpenQASM, also known as QASM) into the qudit form for execution on qudit hardware and provide a method for translating qudit experiment results back into qubit results. We present the comparison of several qudit transpilation regimes, which differ in decomposition of multicontrolled gates: qubit as ordinary qubit transpilation and execution, qutrit with <semantics>d<mspace width="3.33333pt"></mspace>=<mspace width="3.33333pt"></mspace>3</semantics> levels and single qubit in qudit, and ququart with <semantics>d<mspace width="3.33333pt"></mspace>=<mspace width="3.33333pt"></mspace>4</semantics> levels and 2 qubits per ququart. We provide several examples of transpiling circuits for trapped ion qudit processors, which demonstrate potential advantages of qudits.